2014
DOI: 10.1109/tdei.2014.6740724
|View full text |Cite
|
Sign up to set email alerts
|

Electrical treeing behavior of DC and thermally aged polyethylenes utilizing wire-plane electrode geometries

Abstract: This paper presents electrical treeing behavior in low density polyethylene (LDPE) and cross-linked polyethylene (XLPE) after exposure to thermal and DC electro-thermal ageing. Both the ageing and the treeing tests were performed by means of two different types of test objects with wire-plane electrode geometry. One type of the tested objects contained only wire electrode of 10 µm diameter, whereas in the other type the wire electrode was attached through a semiconducting tab. The ageing was performed at 80°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…It has been earlier shown that the influence of the voltage polarity was not significant [9]. In this work -10 kV voltage sources was used for the electro-thermal ageing.…”
Section: Thermal and Electro-thermal Ageingmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been earlier shown that the influence of the voltage polarity was not significant [9]. In this work -10 kV voltage sources was used for the electro-thermal ageing.…”
Section: Thermal and Electro-thermal Ageingmentioning
confidence: 92%
“…Thereafter, the manufactured objects are degassed at 60 °C in vacuum for 7 days. A typical problem occasionally appearing during the preparation is formation of kinks at the wire electrode, but no particular precautions are needed as the trees growing at them can be censored [8,9]. …”
Section: Manufacture Of Test Objectmentioning
confidence: 99%
“…The wire-plane electrode was first presented in [10], and the procedure used in this work was similar to that in [11]. The only difference was that a straight tungsten wire was used here instead of an arc one.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Researchers found that electrical tree was the main reason for insulation degradation during partial discharge process [16]. Many experiments were carried out to characterize electrical tree growth behavior in polymers [17][18][19][20][21]. It was found that the treeing process was affected by many factors including voltage, frequency, temperature, space charge, harmonic distortion and crystallization [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%